THE INFLUENCE OF COMPANY SIZE AND CAPITAL STRUCTURE ON COMPANY PROFITABILITY IN PT. TRISAKTI OTTO PRATAMA IN PALEMBANG - Dandi, Dandi; Rahayu, Endang; Aminus, Rahmi (Jurnal Manajemen, 2024)
This study was conducted to analyze the management of company size (firm size) and capital structure (DER) of distributors and also to re-examine the influence of these variables on profitability with quantitative research with descriptive methods, namely by analyzing and describing financial report data to determine the category of company health at PT Trisakti Otto Pratama Palembang for the period 2017 to 2021.". The objects in this study are company size and capital structure. The data analysis method used in this study is simple linear regression test analysis and multiple linear regression test with the help of the SPSS version 26 program. The results of the study indicate that simultaneously company size and capital structure have a positive and significant effect on profitability. Partially, company size has a positive and significant effect on profitability. While capital structure has a negative and significant effect on profitability at PT Trisakti Otto Pratama Palembang for the period 2017 to 2021. This study has implications that when a company wants profit, the company must be able to use the assets and debts it has optimally in carrying out the company's operational activities.